Bodies and borders : towards a more holistic approach to migrant body - Dunaeva, Aleksandra (Taideyliopiston Teatterikorkeakoulu, 2026)
This thesis explores the concept of the “migrant body” through theatre pedagogy, proposing a holistic, embodied approach to navigating the tensions between “bodies” and “borders”. Drawing on the researcher's personal experience of migration and interdisciplinary frameworks, including anthropology of borders, critical geography and postcolonial theory, the study reimagines borders as dynamic, affective, and relational processes that are specific to the migrant experience. The “migrant body” is therefore conceptualised as a unified field in which cognition, emotion, and corporeality are inseparable. This builds on the work of educators and theorists such as E. Anttila, J. Varto and the artist Trinh T. Minh-ha. The research questions explored in this study are: What kinds of pedagogical and artistic encounters emerge when engaging with borders? What methods does theatre pedagogy offer for articulating embodied migration experiences? Adopting a post-qualitative research framework influenced by poststructuralism and new materialisms, this study views research as an open, process-oriented endeavour. It considers knowledge to be relational, emerging between the researcher, participants, materiality, and the world, rather than an objective reflection of them. The research is grounded in a practice developed through the Bodies and Borders workshop series, which was held at Uniarts Helsinki between November 2025 and March 2026. These workshops provided spaces for collective enquiry in which co-creators explored how borders are experienced, negotiated and transformed through somatic practices, body mapping, object-based work and performative exercises. When reflecting on this practical work, particular attention is given to somatic practices and object-based pedagogy as tools for engaging with the bodily dimensions of migration. The findings suggest that these approaches enable co-creators to reflect on their position within new social contexts and reconsider notions of belonging throughout the process. Interaction with objects in performative settings supports the reinterpretation of lived experience.
Keywords: migrant body; post-qualitative research; embodied learning; somatic practice; border; situated knowledge; Ahmed, Sara; Fischer-Lichte, Erika; Haraway, Donna Jeanne; Braidotti, Rosi; esittävät taiteet; teatteritaide; pedagogiikka; ruumiillisuus; maahanmuuttajat; siirtolaiset; rajat; ruumis; identiteetti; siirtolaisuus; taiteellinen tutkimus; fi=teatteriopettaja|sv=teaterpedagogik|en=Theatre Pedagogy|